Hubungan Health Locus Of Control Dengan Kualitas Hidup Pada Pasien Penyakit Ginjal Kronis Yang Menjalani Hemodialisis Di RSUD Raja Ahmad Thabib - Melania Eka Putri; Utari Christya Wardhani; Indah Purnama Sari (Journal Clinical Pharmacy and Pharmaceutical Science, 2025)
Kidney failure is a serious public health problem, the impact of an unhealthy lifestyle, and the costs of treatment and care are quite expensive. The lives of patients with chronic renal failure are regulated and adapted to the changes caused by the nature of the disease and the methods of its treatment. Hemodialysis carried out by patients can maintain survival and at the same time change the patient's lifestyle. To find out if someone controls compliance, you can use health locus of control. This study aims to determine the relationship between health locus of control and quality of life in chronic kidney disease patients undergoing hemodialysis at Raja Ahmad Thabib Regional Hospital. The design of this research is descriptive quantitative with a cross sectional approach. The results show that there is a relationship between health locus of control and quality of life in chronic kidney disease patients undergoing hemodialysis at Raja Ahmad Thabib Regional Hospital, with a p value of 0.006≤0.05. It is hoped that health workers will carry out treatment for chronic kidney failure patients by providing education, motivation and moral support to patients who are undergoing treatment and providing psychological counseling for patients who need it.